KEMAMPUAN DASAR MATEMATIKA BERBANTUAN BOOKLET UNTUK MEREMEDIASI KESALAHAN PENYELESAIAN SOAL PESERTA DIDIK DI SMP - Heryani, Eni; Sahala, Stepanus; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to determine the effectiveness of remediation reduction problem solving error on the material in the straight motion of SMP Negeri 12 Pontianak by used learning basic repetition of mathematics assisted booklet. The form of research is pre-experimental design with one group pretest-posttest design. This study involved 32 students of class VIII taken with intact group technique. Instrument of research in the form of 2 test description that is test of basic ability of mathematics and test of problem solving problem of student in matter of straight motion. The result of basic mathematics skill analysis during pretest shows the basic ability of mathematics that most controlled by the students is the addition and subtraction operation of integer (65,62%), while the basic ability of mathematics which is difficult to be mastered is change the mathematics equation (10,94%). However, when the posttest obtained the highest improvement of basic mathematical ability on the indicator change the mathematical equation by 32.81%. The decrease of problem solving problem of students on the straight motion material based on the calculation obtained by decrease of 57,63% for each learner, and decrease of error of each indicator equal to 57,32%, with decrease of the lowest error that is at counting operation error (45,06%) . From the calculation of the price of the proportion of the decline in the number of student error obtained 57.73% results and based on the criteria of interpretation effectiveness score by Riduan, the level of effectiveness of basic math skills in reducing the number of errors in the completion of the problem of straight motion including enough category. The results of the study are expected to be an alternative in efforts to remedy the problem solving problems experienced by learners.Keywords : Remediation, basic ability of mathematics, reduction of physics problem solving, straight motion.